O vampiro romântico, uma questão estética: uma história das representações através do mito - Korasi, Fabricio Pereira (2014)
This paper analyzes the characteristics of the aesthetics of romanticism through the vampire myth. An analytic trajectory since vampires, or undead, from Antiquity until the construction of the Vampire Romantic Classic, created by Bram Stoker: Dracula. From that stereotype created, the figure of romanticism and the vampire were reproduced and adapted to prevailing social time, culminating in the creation of the Vampiro Malhação. All this history is important to understand how the aesthetic of romanticism are present until the present day